Taxonomic revision of the genus Probolomyrmex Mayr, 1901 (Hymenoptera: Formicidae: Proceratiinae) for the Neotropical Region - Oliveira, Aline M.; Feitosa, Rodrigo M. (Zootaxa, 2019)
We revise the taxonomy of the ant genus Probolomyrmex for the Neotropical region. Eight species are recognized, four of them already known: P. boliviensis, P. brujitae, P. guanacastensis, and P. petiolatus. Four new species are described: P. cegua sp. n., P. dentinodis sp. n., P. kelleri sp. n. and P. lamellatus sp. n. We present complete descriptions and redescriptions for all the species, including diagnoses, comments on the taxonomic history and biology, high-quality images, and scanning electron microscope micrographs for diagnostic anatomic structures. In addition, distribution maps and an illustrated identification key are provided.